2009
DOI: 10.1093/mutage/gep055
|View full text |Cite
|
Sign up to set email alerts
|

An ECVAG trial on assessment of oxidative damage to DNA measured by the comet assay

Abstract: The increasing use of single cell gel electrophoresis (the comet assay) highlights its popularity as a method for detecting DNA damage, including the use of enzymes for assessment of oxidatively damaged DNA. However, comparison of DNA damage levels between laboratories can be difficult due to differences in assay protocols (e.g. lysis conditions, enzyme treatment, the duration of the alkaline treatment and electrophoresis) and in the end points used for reporting results (e.g. %DNA in tail, arbitrary units, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 14 publications
(17 reference statements)
2
50
0
2
Order By: Relevance
“…, Johansson et al . ). However, although the comparison of results obtained from in vitro and in vivo genotoxicity assays indicates that the comet assay gives relevant information, it is important to emphasize that in vitro assays do not take into consideration the complex homoeostatic situation that occurs in vivo (Ribeiro , Liuyun et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Johansson et al . ). However, although the comparison of results obtained from in vitro and in vivo genotoxicity assays indicates that the comet assay gives relevant information, it is important to emphasize that in vitro assays do not take into consideration the complex homoeostatic situation that occurs in vivo (Ribeiro , Liuyun et al .…”
Section: Discussionmentioning
confidence: 97%
“…Briefly, after trypsinization, cells were mixed with 300 ml of low melting point agarose (0.8% w/v in PBS) and loaded onto a normal pre-coated microscopic slide (normal melting point agarose 1% w/v in water). After lysis at 4 C (2.5 M NaCl, 100 mM NA 2 EDTA, 10 mM Tris supplemented with 1% Triton-X100 and 10% DMSO just before use), slides were rinsed twice with enzyme buffer (40 mM HEPES, 100 mM KCl, 0.5 mM EDTA, 0.2 mg/ml BSA; pH 8) prior to incubation with 75 ml formadidopyrimidine DNA glycosylase (FPG; New England Biolabs, Leusden, The Netherlands) for 35 min at 37 C. FPG was chosen because of the great efforts that recently have been made by the European Comet Validation Group (ECVAG) to validate this method (Johansson et al 2010. Furthermore 8-oxo-2¢deoxyguanosine (8-oxo-dG) is the most common oxidative lesion (Pluskota-Karwatka 2008).…”
Section: Alkaline Comet Assaymentioning
confidence: 99%
“…While it has been demonstrated that several technical parameters, such as slide preparation, electrophoresis, or scoring of comets can have a strong impact on the assay results (Forchhammer et al, ; Johansson et al, ; Azqueta et al, ), little is known on how initial steps affect the comet assay results. Thus, we evaluated how variations during the processing of liver tissue (meaning from necropsy and tissue sampling until single liver cells are embedded in an agarose layer on the glass slide) impact DNA migration in samples from untreated animals.…”
Section: Introductionmentioning
confidence: 99%